Effect Of Pumpkin Leaves On Milk Production Of Breastfeeding Mother - Warsinah Warsinah; Erna Widyastuti; Sri Wahyuni (Poltekkes Kemenkes Semarang, 2022)
Background: Pumpkin (Cucurbita Mochata Durch) leaves is considered as traditional food that can increase breast milk production. Only a few people know the benefit of this local wisdom in Technical Implementing Service Unit (UPTD) of Dayeuhluhur Community Health Center I Cilacap Regency. Consequently, a research is required to examine its effect. This research is to examine the effect of pumpkin leaves on breast milk production of postpartum women. Methods:This research used quasi experiment method with post-test control group design. There were 22 breastfeeding mother recruited with purposive sampling and divided into treatment group (11 breastfeeding mother) and control group (11 breastfeeding mother). The respondents of each group were selected randomly. The research instruments were Omened digital weighing scale and observation sheets. Breast milk production was measured based on the increase of infant weight in 7 days during treatment and converted to breast milk volume in ml. Data Analysis using Independent t–Test. Results:The research results show a significant effect of pumpkin leaves on breast milk production of postpartum women with Independent t-Test statistical test results (p-value 0.001) < (0.05). Show that the average of breast milk volume on treatment group is 103.29 ml and on control group is 45.15 ml. It is obtained from the measurement of infant weight that increases by 363.73 gram on the treatment group and 159.00 gram on the control group with an average difference of 204.73. Conclusion: The findings of this research show that pumpkin leaves can be used as an alternative daily menu for postpartum women and solution for midwives in handling postpartum women with inadequate breastmilk production